Quality of youth friendly sexual and reproductive health Services in West Gojjam Zone, north West Ethiopia: with special reference to the application of the Donabedian model - Alemtsehay Mekonnen Munea; Getu Degu Alene; Gurmesa Tura Debelew (BMC, 2020)
Abstract Background Although there has been momentum in implementing sexual and reproductive health services in Ethiopia, young people remain underserved despite their demonstrated needs. Quality care improves utilization of health service and increases the likelihood of obtaining ongoing care. However, little is known about the quality of youth-friendly sexual and reproductive health service in Ethiopia. Therefore, this study sought to investigate the quality of youth-friendly sexual and reproductive health service in West Gojjam Zone, North West Ethiopia. Methods Health facility-based cross-sectional study was conducted in West Gojjam zone in 2018 to assess the quality of the service using the Donabedian model. The assessment was done through the triangulation of multiple methods: simulated client study; structured interviews with service providers; observations; and key informant interview with providers and expertise. Fifty-four visits were made to 18 randomly selected health facilities by three simulated clients trained to present three different scenarios (i.e., adolescent with sexually transmitted infection, pregnancy test request and a lady with dry cough). Data were entered and analyzed using SPSS version 21. Facility visit score of ≥ 75% in all quality component categorized as "good quality" otherwise classified as performing below the standard. Thematic analysis was done to analyze qualitative data. Results In this study, none of the health facilities achieved ≥ 75% in the three components of quality measurement. From 18 health facilities, 6(33.3%) provided low quality in all domains. Process component, which measures client-provider interaction and privacy/confidentiality, was the most compromised one. However, a promising result was reported in the input quality that measured the availability of trained providers, drugs, and supplies. The presence of community-based health insurance and age driven comprehensive youth-friendly service delivery approach were identified as challenges to deliver quality services. Conclusions The quality of the service ranges from low to medium, with adolescent related elements performing poorly. Minor renovations of health facilities, training on client handling, and contextual modifying the age driven youth-friendly service approach may improve the quality of the services.